Polluter pays principle: did the polluter in Kim Kim river pollution trial get off too easy? - Ho Nyuk Onn @ Ariffin, Mariani (CLJ Unreported Series, 2024)
The paper summarizes facts and judgments of court cases arising from the 2019 Kim Kim River pollution. It then analyzes the court cases in light of the polluter pays principle before concluding the discussion.